2018
DOI: 10.1007/s11936-018-0607-1
|View full text |Cite
|
Sign up to set email alerts
|

Transradial Artery Access in Percutaneous Coronary Intervention for ST-Segment Elevation Myocardial Infarction and Cardiogenic Shock

Abstract: Early revascularization is the gold standard for management of patients with ST-elevation myocardial infarction (STEMI) and cardiogenic shock (CS). The use of transradial artery access (TRA) in percutaneous coronary intervention (PCI) has increased in recent years and has emerged as a safe and effective approach to PCI in high-risk patients, with advantages in reduced major bleeding events, other peri-procedural complications, and all-cause mortality when compared with transfemoral artery access (TFA). Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
1
2
0
1
Order By: Relevance
“…To our best knowledge, the presented study for the first time provides a clinical view from a national perspective on the impact of vascular access site on clinical outcomes in STEMI with CS in a contemporary unselected cohort of patients. Our analysis is consistent with the results of former studies [11,[19][20][21][22][23][24]. Favorable outcome in RA was confirmed in a large meta-analysis of 6 observational studies [11].…”
Section: Discussionsupporting
confidence: 92%
“…To our best knowledge, the presented study for the first time provides a clinical view from a national perspective on the impact of vascular access site on clinical outcomes in STEMI with CS in a contemporary unselected cohort of patients. Our analysis is consistent with the results of former studies [11,[19][20][21][22][23][24]. Favorable outcome in RA was confirmed in a large meta-analysis of 6 observational studies [11].…”
Section: Discussionsupporting
confidence: 92%
“…MI is one of the cardiovascular events associated with high mortality worldwide. After MI, inflammatory mediators are released from the myocardium as a response to injury, postinjury repair, and adaptation (1)(2)(3)(4). Our previous study reported that plasma IL-38 levels in patients with ST-segment elevation MI are positively correlated with CRP, cardiac troponin I (cTNI), and N-terminal pro-brain natriuretic peptide (NT-proBNP) but weakly negatively correlated with left ventricular ejection fraction (9).…”
Section: Role Of Interleukin-38 In Myocardial Infarctionmentioning
confidence: 99%
“…Myocardial infarction (MI), an ischemic injury of the myocardium following the obstruction of coronary artery flow, is one of the leading causes of death worldwide and is closely related to inflammation. After MI, various inflammatory mediators released by the ischemic myocardium are involved in tissue repair and related adaptive responses (1)(2)(3)(4). The development of necrotic myocardium after MI can be categorized into 3 overlapping stages: the inflammatory stage, the proliferative stage, and the mature stage.…”
Section: Introductionmentioning
confidence: 99%
“…Pastaruoju metu populiarėja PKI atlikimas per stipininę arteriją (transradialinis kelias). Daugėja įrodymų, kad procedūrai renkantis stipininę arteriją, sumažėja gausaus kraujavimo ir ateroembolinių inkstų kraujagyslių komplikacijų rizika [3]. Nors PKI per stipininę arteriją turi daug privalumų, tačiau galimos ir komplikacijos, tokios kaip dūrio vietos kraujavimas, stipininės arterijos okliuzija ir kraujosruvos susidarymas.…”
Section: įVadasunclassified